Mantidflies of Colombia (Neuroptera, Mantispidae) - Ardila-Camacho, Adrian; García, Alexander (Zootaxa, 2015)
This study revises the Mantispidae of Colombia. 151 adult specimens of 12 entomological museums of Colombia were examined and identified. On the basis of the specimens studied and a comprehensive literature search, it is determined that 20 nominal species (including two doubtful records) plus four proposed as new to science, in ten genera (Anchieta, Plega, Trichoscelia, Gerstaeckerella, Buyda, Climaciella, Dicromantispa, Entanoneura, Leptomantispa, and Zeugomantispa) and, three subfamilies (Symphrasinae, Drepanicinae, and Mantispinae) occur in Colombia. In addition, A. eurydella (Westwood), C. amapaensis Penny and P. fasciatella (Westwood) are redescribed, providing complementary information to the original descriptions. A list of Colombian Mantispidae, distribution maps and taxonomic keys to subfamilies, genera and species are included. Illustrations of the external morphology and male genitalia are provided for selected species. The taxonomic status of P. hagenella (Westwood) is discussed, and its diagnostic characters are redefined. Anchieta remipes (Gerstaecker) is newly transferred to this genus from Trichoscelia.